Comparison of bone mass and quality determinants in adolescents and young adults with juvenile systemic lupus erythematosus (JSLE) and juvenile idiopathic arthritis (JIA). (November 2014) - Stagi, S; Cavalli, L; Bertini, F; Signorini, C; Matucci Cerinic, M; de Martino, M; Brandi, M L; Falcini, F
Background: Few prospective data have been published on the comparison of bone density and quality in homogeneous groups of patients with juvenile systemic lupus erythematosus (JSLE) and juvenile idiopathic arthritis (JIA). Objective and hypothesis: The objective of this study is to perform a longitudinal evaluation of the prevalence and the characteristics of bone mass and quality and to evaluate the differences on the bone parameters, using DXA, pQCT and QUS. Population and/or methods: Forty-three JSLE patients (35 females, 8 males, median age 18.8, range 14.0–34.1 years) have been studied with DXA, pQCT and QUS scans and compared with 138 JIA patients (112 females, 26 males, median age 18.9, range 13.4–33.2 years), and 79 controls (59 females, 20 males; median age 19.3, range 13.5–36.5 years). Of these, 39 patients (32 females and 7 males, median age 20.3, range 16.6–36.8 years) with JSLE were followed longitudinally and compared with 131 patients (108 females, 23 males median age 20.7, range 15.8–37.1 years) with JIA and 63 controls (48 females, 15 males; median age 21.9, range 15.5–38.3 years). Results: JSLE patients have a higher bone cortical density (CrtBMD) than controls and JIA patients ( p  < 0.005). However, JSLE and JIA patients have a significantly reduced bone trabecular density (TrbBMD) compared to controls ( p  < 0.0001), with no differences between JSLE and JIA. In addition, JIA patients show a significantly reduced muscle area (MuscleCSA) compared to JSLE and controls ( p  < 0.001). Conversely, fat area (FatCSA) is significantly increased both in JIA and JSLE patients when compared to controls ( p  < 0.001), with no differences between the JSLE and JIA groups. Analogous results are observed in the polar resistance to stress (SSIp). On longitudinal evaluation, contrary to CrtBMD, the difference between BMAD SDS, TrbBMD, MuscleCSA and FatCSA remains unchanged; in JSLE patients, SSIp is stable in comparison to JIA and controls without any difference between the two groups. Conclusions: The evaluation of bone density and structure parameters in JSLE patients highlights significant differences compared with JIA patients and controls. These data might indicate a different pathogenesis of bone damage in the two entities, and suggest a different diagnostic and therapeutic approach to improve the peak bone mass.